Upaya Percepatan Penanganan Kondisi Substandard Submarine Pipeline Penerimaan Avtur menggunakan Metode Double-Ended Draining dan Oil Bubble Trap - Fuad Al Amien; Wahyu Putra HK; Andre Sumanta; Jhodi Irawan; Aris Setiyawan; Tahta Adhitama; Vrisco Harjanto (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Submarine pipelines are vital infrastructures in aviation fuel distribution, carrying high risks of operational disruption, safety issues, and environmental pollution. In 2025, the aviation fuel receiving submarine pipeline at Integrated Terminal Ampenan was deformed due to mechanical pulling by MT Anargya I, causing system shutdown. This incident created risks of seawater intrusion, marine pollution, and potential fuel shortages at Lombok International Airport. This study evaluates the effectiveness of applying a double-ended draining method combined with an oil bubble trap as a fast, safe, and sustainable solution for submarine pipeline repair. Using a case study and descriptive-analytical approach based on the Continuous Improvement Program (CIP), the research analyzed quality, cost, delivery, safety, environmental, and workforce aspects. The results showed the method effectively drained aviation fuel without seawater contamination, prevented marine spills, maintained fuel quality within specifications, and completed repairs before critical stock levels were reached. Additionally, it provided significant cost savings compared to emergency supply operations and achieved zero safety incidents and environmental pollution. The integration of double-ended draining and oil bubble trap proved to be an effective, adaptive innovation with strong potential for replication and standardization in other aviation fuel submarine pipeline systems.